2002
DOI: 10.1016/s0925-4773(01)00579-2
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for AP-2α in cardiac outflow tract morphogenesis

Abstract: Most developing structures that express the transcription factor gene AP-2alpha are compromised in AP-2alpha mutant mouse embryos. Since the cardiac neural crest population is one prominent site of AP-2alpha expression, and because the neural crest is known to be required for normal cardiac morphogenesis, we have investigated the involvement of AP-2alpha in cardiac development. All AP-2alpha-deficient embryos examined had malformations of the outflow tract of the developing heart: most had double outlet right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 26 publications
10
93
0
Order By: Relevance
“…All mice analyzed exhibited a ventricular septation defect that was closely associated with outflow tract malformations that ranged from common arterial trunk to double outlet right ventricle. Similar heart phenotypes have been observed in many different knockout mice and have been found to be incompatible with postnatal life (1,5,13,23,34).…”
Section: Discussionsupporting
confidence: 73%
“…All mice analyzed exhibited a ventricular septation defect that was closely associated with outflow tract malformations that ranged from common arterial trunk to double outlet right ventricle. Similar heart phenotypes have been observed in many different knockout mice and have been found to be incompatible with postnatal life (1,5,13,23,34).…”
Section: Discussionsupporting
confidence: 73%
“…7). TFAP2A has previously been shown to be expressed by premigratory and migratory cranial NC cells and be important in NC induction, proliferation and differentiation in mice, zebrafish and Xenopus, as well as avian facial tissue growth (Mitchell et al, 1991;Chazaud et al, 1996;Schorle et al, 1996;Shen et al, 1997;Pfisterer et al, 2002;Brewer et al, 2002;Luo et al, 2003;Knight et al, 2003Knight et al, , 2004Barrallo-Gimeno et al, 2004;Li and Cornell, 2007;Wang et al, 2011). We have previously shown that when leaders are prevented from migrating into the target site by a physical barrier, trailing NC cells sense the paused leaders, reroute around the barrier and become the new leaders (Kulesa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To generate a conditional knockout of AP-2␣ in the lens placode, mice heterozygous for the Tcfap2a:LacZ KI allele (maintained on an outbred Black Swiss genetic background), a null allele (Brewer et al, 2002), were bred with heterozygous Le-Cre mice (maintained on an FVB/N genetic background) that expressed Cre-recombinase specifically in cells within the early lens placode (Ashery-Padan et al, 2000). Resultant progeny from this cross, heterozygous for both the Cre transgene and the Tcfap2a:LacZ KI allele, were then bred with mice homozygous for the Alflox allele (maintained on a mixed 129/ Black Swiss background), an allele of Tcfap2a in which paired loxP sites flank a region encoding a critical region of the DNA binding domain (Brewer et al, 2004).…”
Section: Generation Of Mouse Linesmentioning
confidence: 99%